Design and models of helical needle geometries for core biopsies. (February 2019) - Giovannini, Marco; Cao, Jian; Ehmann, Kornel
Abstract: Biopsy needles are standard medical devices for extracting biological tissue with the purpose of diagnosing a specific anomaly such as cancerous masses, or lumps. The outcome of these procedures greatly relies on the quality of the samples which, in turn, depends on the forces acting on the needle during its insertion. In this scenario, the design of the needle tip plays a fundamental role in determining the cutting forces. Yet, since the dawn of modern medicine, only a few studies have proposed novel needle tip configurations. In this study, the geometry of biopsy needles is investigated, and helical cutting edges characterized by a three-dimensional (3D) profile are conceived. Mathematical models were formulated to compute the cutting angles and the tissue fracture forces. The proposed methodology is general and can be applied to any 3D needle cutting edge geometry. The utility of the helical geometry was demonstrated on a 14-gauge hollow needle which is generally used during breast biopsies. Experimental insertions were performed at different cutting speeds on phantom tissue. The results show that helical needles generate lower cutting forces than commercial needles and recommendations are formulated for the selection of their cutting parameters. The outcome of this investigation is applicable to biopsy examinations in which a hollow needle is adopted to acquire soft tissue samples.